Computer simulation for subcritical convection in multi‐component alloys - Kolmychkov, V. V.; Mazhorova, O. S.; Popov, Yu. P. (Mathematical Modelling and Analysis, 2006)
Subcritical convection with hexagonal flow pattern is registered in 3D computer simulation of convective mass transfer in ternary solution under phase transition conditions. The calculations are evaluated by the classical theory of hydrodynamic stability and display a good agreement with linear and finite amplitude stability analysis. Key words: convective instability, subcritical convection, computer simulation.First Published Online: 14 Oct 2010